2021
DOI: 10.3390/md19030153
|View full text |Cite
|
Sign up to set email alerts
|

Chitin Synthesis and Degradation in Crustaceans: A Genomic View and Application

Abstract: Chitin is among the most important components of the crustacean cuticular exoskeleton and intestinal peritrophic matrix. With the progress of genomics and sequencing technology, a large number of gene sequences related to chitin metabolism have been deposited in the GenBank database in recent years. Here, we summarized the genes and pathways associated with the biosynthesis and degradation of chitins in crustaceans based on genomic analyses. We found that chitin biosynthesis genes typically occur in single or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(30 citation statements)
references
References 76 publications
0
30
0
Order By: Relevance
“…Amino acid sequence alignment showed that two CHS signature motifs with the respective consensus sequences of EDR and QRRRW in the central catalytic domains are conserved in TmCHS1 and TmCHS2 (Merzendorfer & Zimoch, 2003) (Supporting Information: Figure S2). Another motif "WGTRE" with two conserved amino acids (T and W) that play a catalytic role, thought to be closely related to enzyme activity, is also present in both of them (Merzendorfer & Zimoch, 2003;Zhang et al, 2021). Phylogenetic analysis based on amino acid sequences showed that two members of the CHSs from different insect orders were distinctly grouped into different phylogenic branches, indicating the origin of both CHS1 and CHS2 genes from one ancestral gene (Figure 2).…”
Section: Structural and Phylogenetic Analysis Of Chitin Metabolism Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Amino acid sequence alignment showed that two CHS signature motifs with the respective consensus sequences of EDR and QRRRW in the central catalytic domains are conserved in TmCHS1 and TmCHS2 (Merzendorfer & Zimoch, 2003) (Supporting Information: Figure S2). Another motif "WGTRE" with two conserved amino acids (T and W) that play a catalytic role, thought to be closely related to enzyme activity, is also present in both of them (Merzendorfer & Zimoch, 2003;Zhang et al, 2021). Phylogenetic analysis based on amino acid sequences showed that two members of the CHSs from different insect orders were distinctly grouped into different phylogenic branches, indicating the origin of both CHS1 and CHS2 genes from one ancestral gene (Figure 2).…”
Section: Structural and Phylogenetic Analysis Of Chitin Metabolism Genesmentioning
confidence: 99%
“…Most insect HEXs belong to the GH20 family, which can be divided into six subfamilies: NAG1, NAG2, FDL (fused lobe gene), Hex (hexosaminidase), HexD‐like, and O‐linked N‐acetylglucosaminidase (O‐GlcNAcase) (Xi, Pan, Zhang et al, 2015). Similar to CHSs and CDAs, CHTs and HEXs show distinct expression among tissue sites and developmental stages, indicating biological activities in various physiological functions (Tetreau et al, 2015; Xi, Pan, Zhang et al, 2015; Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, chitin exhibits a high degree of thermodynamic stability. The poor solubility of chitin in solvent extraction makes the extraction process difficult and laborious (Zhang et al, 2021). With advances in technology and a better understanding of its physiological and biological properties, chitin can be deacetylated and converted into chitosan (CS), a watersoluble polysaccharide (El Knidri et al, 2018).…”
Section: Chitin and Chitosanmentioning
confidence: 99%
“…Its main functions include: first, it plays an important role in the growth and development of insects, especially in the process of periodic molting ( Arakane and Muthukrishanan, 2010 ); Second, as the main component of the body surface or trachea epidermis, it protects the internal organs of insects and prevents the invasion of foreign toxins and pathogens to organisms ( Hegedus et al, 2009 ; Doucet and Retnakaran, 2012 ). Based on the important role of chitin in insect growth and development, and the absence of chitin in higher animals, the control of chitin synthesis and degradation has become a safe target for the development of new pesticides ( Oyeleye and Normi, 2018 ; Zhang X. et al, 2021 ; Zhang J. Y. et al, 2021 ; Wang et al, 2022 ). In addition, the purified chitinase has certain insecticidal activity ( Suganthi et al, 2017 ), which has attracted more and more attention.…”
Section: Introductionmentioning
confidence: 99%
“…If chitinase is continuously expressed and acts, the synthesis of chitin may still be affected after the formation of new epidermis, thus causing the development of insects to be blocked and even death ( Xi et al, 2015 ; Liu et al, 2017 ). Many studies have found that once the expression of chitinase gene was inhibited, the development of insect larvae such as molting, pupation, adult eclosion and wings would be affected ( Zhu et al, 2008b ; Pesch et al, 2016 ; Dong et al, 2020 ; Zhang X. et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%